Abrupt Freshening Since the Early Little Ice Age in Lake Sayram of Arid Central Asia Inferred From an Alkenone Isomer Proxy. Issue 16 (14th August 2020) - Yao, Yuan; Lan, Jianghu; Zhao, Jiaju; Vachula, Richard S.; Xu, Hai; Cai, Yanjun; Cheng, Hai; Huang, Yongsong
Abstract: Hydroclimatic variations of arid central Asia (ACA) significantly impact regional ecosystems and human civilizations. Here we present a lake water salinity record of the last 3, 000 years from Lake Sayram in the core area of ACA using a new alkenone isomer‐based RIK37 index. Our record shows an abrupt decrease in salinity by more than 5‰ since the "early" Little Ice Age (LIA) (about CE 1150), which can be attributed to the combined effect of regional wetting, cooling, and topographic features. Combined with other moisture records in the region, we find two periods of relatively wet conditions during CE 1150–1550 and 1850 to present, which may be linked to Arctic sea ice expansion due to natural variability and, from CE 1950, anthropogenically induced warming. The wet conditions during CE 1206–1260 may have favored the spread of the Mongol Empire across the entire core area of ACA. Plain Language Summary: Arid central Asia (ACA), one of the largest arid zones in the world, suffers from water resource scarcity, which impacts the regional ecosystems and human civilizations. Reconstructions of lake water salinity in ACA can provide valuable information on past overall hydroclimatic changes, which is of crucial importance for our understanding of past and future climates. Here we apply a new salinity proxy, based on the lipid biomarkers of haptophyte algae, to quantitatively reconstruct salinity changes of the last 3, 000 years from Lake Sayram in the core area of ACA and find an abrupt freshening of lake water since the early Little Ice Age (LIA). Our reconstruction, together with other moisture records in the region, indicate relatively wet conditions at two intervals during CE 1150–1550 and 1850 to present, which are associated with natural and anthropogenic forcing. During the period of CE 1206–1260, the favorable wet conditions may have aided the spread of the Mongol Empire across the entire core area of ACA. Key Points: We present the first application of an alkenone isomer‐based RIK37 index as salinity proxy in Lake Sayram Lake water freshened abruptly since the early Little Ice Age Wet conditions during CE 1150–1550 and 1850 to present may be related to Arctic sea ice expansion and anthropogenically induced warming